.TABON WOOD STRUCTURE MODIFICATION WITH PENNINERALIZATION OF MGC03 COMPOUND - Chandra, Christopher
Jabon wood is a low quality wood. In order to be used on an industrial scale, Jabon wood must be further processed, especially in terms of its mechanical strength. One important factor that affects its mechanical strength is density. Good quality wood generally has a higher density value than low quality wood. Therefore, in this study the density of Jabon wood will be increased, aim in order to improve its mechanical strength. In low quality wood, there are many wood cavities in large sizes. This wood cavity is intended to be filled in order to increase its density. Cavities were filled using the mineral MgCO3 using two methods. The first method used one step immersion, using MgCO3 supersaturation solution. The second method, used two stages of immersion using a solution of MgCl2 and Na2CO3. Wood specimens after immersion are dried, then its mass, volume and density are measured. In the one stage immersion method, the mass, volume, and density have a downward trend. Whereas in the two stage immersion method, the mass profile of the sample rose up to 142%, the volume increased by 4.79%, and the density increased by 130.9 %. Unfortunately, these data are not in line with the results of wood compression test. It can be concluded that all samples that had been immersed, have decreased mechanical strength, even the control specimens have better values. The decrease in mechanical strength of specimens compared to controls in the one-stage and two- stage methods is 13% and 34%, respectively. This was allegedly caused by the big amount of water in the sample, in the sense that the sample was subjected to compression testing, the water content was not below the fiber saturation point, resulting in an unfavorable wood strength profile. Also, there are differences in the size of the wood cavity between Jabon wood, and the previously studied wood, Pinus and Sesendok. Jabon wood cavity size that is larger. It is more difficult to achieve local supersaturation conditions, compared to wood with smaller pore.